Diagnóstico del ambiente laboral de los servidores públicos del Gobierno Autónomo Descentralizado Municipal San Felipe de Oña, periodo de estudio 2017 - De la Rosa Borbor, Cynthia Tatiana (2018)
This research work is structured as provided by the Regulation of Academic Regime of the National University of Loja and the Guidelines of the Public Administration Career, has a review of literature that is divided into theoretical framework and referential framework, to support the study entitled "Diagnosis of the work environment of public servants of the San Felipe de Oña Municipal Decentralized Autonomous Government, 2017 period". To make this diagnosis, there was aa target population made up of all the public servants of the GADM, which are a total of 38 people, of whom 37 were surveyed to identify their perspective of the work environment as employees, however for determine the perspective as heads were interviewed to the maximum authority of the Canton and to the 6 departmental directors of the institution. Once the research techniques were applied, the result was that in terms of physical, structural, interpersonal, personal and organizational behavior factors, all of them are in a satisfactory range, thus concluding with the determination of a satisfactory work environment for the public servants of the institution. This work finishes with the respective recommendations for each conclusion obtained, emphasizing the variables of each factor that gave negative results, likewise a periodic evaluation of the work environment of the institution is suggested.